2007
DOI: 10.1515/cclm.2007.004
|View full text |Cite
|
Sign up to set email alerts
|

Correction of patient results for Beckman Coulter LX-20 assays affected by interference due to hemoglobin, bilirubin or lipids: a practical approach

Abstract: The influence of interference by hemolysis, icterus and lipemia on the results of routine chemistries may lead to wrong interpretations. On Synchron LX-20 instruments (Beckman Coulter) serum or plasma indices can be used as reliable semi-quantitative measures of the magnitude of such interference. In an article recently published in this journal, we presented the results of a multicenter study carried out in Dutch hospitals in which we determined cutoff indices for analytes above which analytically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 16 publications
1
27
0
5
Order By: Relevance
“…Linear regression analysis revealed a 0.38 mEq/L (95% confidence interval, 0.36-0.40; conversion to SI units: 1 mEq/L 5 1 mmol/L) potassium increase per increment in H-index for capillary samples, which is more than twice as high as the 0.17 mEq/L (95% confidence interval, 0.16-0.17) increase found for venous samples. The latter result corresponds well with the potassium increase of 0.14 mEq/L per H-index increment described by Vermeer et al, 3 thereby supporting the validity of the current method. The identical offset of 4.1 mEq/L indicates that there are no intrinsic differences in potassium levels between venous and capillary samples, which is in correspondence with previously published results.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Linear regression analysis revealed a 0.38 mEq/L (95% confidence interval, 0.36-0.40; conversion to SI units: 1 mEq/L 5 1 mmol/L) potassium increase per increment in H-index for capillary samples, which is more than twice as high as the 0.17 mEq/L (95% confidence interval, 0.16-0.17) increase found for venous samples. The latter result corresponds well with the potassium increase of 0.14 mEq/L per H-index increment described by Vermeer et al, 3 thereby supporting the validity of the current method. The identical offset of 4.1 mEq/L indicates that there are no intrinsic differences in potassium levels between venous and capillary samples, which is in correspondence with previously published results.…”
Section: Resultssupporting
confidence: 90%
“…3,4 Based on the linear relation between potassium and H-index, correction factors might be derived to adjust the measured potassium level to the extent of hemolysis. [3][4][5][6][7][8][9][10][11][12][13][14][15] Although this would produce representative potassium values in most cases, it fails in cases of intravascular hemolysis. Given that intravascular hemolysis is rare (less than 2% of the hemolytic samples, as shown for an Italian academic hospital 6 ), potassium correction based on high H-indices is not justified in these cases.…”
mentioning
confidence: 99%
“…globin-based oxygen carriers (14), which would ultimately help diminish uncertainty in the preanalytical phase, enhance the quality in laboratory diagnostics, and reduce the chance of errors that can jeopardize the patient safety (7). Although the approach has been previously questioned (7), it is necessary to mention that the availability of quantitative results of hemoglobin in the samples might allow the use of formulas for correcting biases due to interference from hemolysis (15). Although most preanalytical workstations and clinical chemistry platforms are now equipped with automatic systems for detecting, and some for quantitating interferents, no studies have previously assessed imprecision and reproducibility of these measures among facilities and, especially, among different instruments and manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has compared preanalyte and postanalyte measurements on the Beckman Synchron LX-20, after artificial spiking of nonlipemic samples with the synthetic lipid Intralipid (Uppsala, Sweden). 4 In this study, no discordance between recovery with ultracentrifugation and LipoClear was observed with sodium or total protein, highlighting potential limitations for Intralipid as a universal substitute for assessing endogenous lipemic interferences. Additionally, 78% of LipoClear-treated samples showed lower lipemia indices after treatment than did their paired ultracentrifuged specimens, suggesting a more-complete removal of interfering lipids.…”
mentioning
confidence: 54%